1959
DOI: 10.1177/004051755902901111
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Epoxides with Cotton Cellulose in the Presence of Sodium Hydroxide

Abstract: The reactions of various commercially available epoxides with cotton cellulose in the presence of sodium hydroxide have been investigated at 25°, 50°, and 95° C. The effects of solvents and alkali content of the yarn steep on the epoxy add-on have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1961
1961
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Washing the sodium cellulose with dry ethanol to remove excess aqueous NaOH prior to the reaction was found to have no effect on the product, POSS content, or product yield. This is in contrast with the phenyl glycidyl ether reactions examined by McKelvey et al (1959); who found that the presence of some water was necessary to swell the cellulose and facilitate the reaction in toluene. It was found through FTIR and TGA analyses (see Section 3.4) that the final products required extensive washing to remove unbound residual POSS; so products were soxhlet extracted for 48 h using the same solvent as the reaction.…”
Section: Reaction Conditionsmentioning
confidence: 59%
See 1 more Smart Citation
“…Washing the sodium cellulose with dry ethanol to remove excess aqueous NaOH prior to the reaction was found to have no effect on the product, POSS content, or product yield. This is in contrast with the phenyl glycidyl ether reactions examined by McKelvey et al (1959); who found that the presence of some water was necessary to swell the cellulose and facilitate the reaction in toluene. It was found through FTIR and TGA analyses (see Section 3.4) that the final products required extensive washing to remove unbound residual POSS; so products were soxhlet extracted for 48 h using the same solvent as the reaction.…”
Section: Reaction Conditionsmentioning
confidence: 59%
“…Nanofibrillated cellulose fibers were modified with a glycidyl POSS compound using a procedure similar to that reported for phenyl glycidyl ether cellulose (McKelvey, Webre, & Klein, 1959). Cellulose (1 g) was alkaliated using a 15% by mass aqueous NaOH solution (20 mL) for 1 h. The Na-cellulose was filtered using a sintered glass crucible (4-8 m), then was thoroughly washed with dry ethanol and filtered until its wet uptake was 200% by mass.…”
Section: Modification Of Cellulosementioning
confidence: 99%
“…Analyses of fabrics treated with potassium thiocyanate, sodium thiosulfate, sodium sulfite, and an imidazoline derivative indicate all to be coreactants. These analyses, recorded in Table II, show that an appreciablẽ (9). Untreated cotton (0) also is shown.…”
Section: Screening Of C Oreodont Curing Agentsmentioning
confidence: 76%
“…It was noted by Mercer that alkali-treated cellulose exhibits, among other things, greater moisture regain and greater depth of color in dyeing (greater reactivity), probably due to newly freed hydroxyl groups. This greater reactivity has been pointed out [36] as a reason for the maxima in weight gain of various epoxides obtained at maximum alkali swelling with cotton yarn.…”
Section: Effect Of -Ilkali On Cottonmentioning
confidence: 89%
“…' 4. E~o.rides and Wet Creasr R~~oz~c~r~Õ ne must exercise care in comparing epoxide finishes with formaldehyde finishes, because here we are dealing with a class of compounds that vary widely in reactivity for reasons pointed out previously [36,38,40].…”
Section: Cotton Cell Ulose ~And Water 'mentioning
confidence: 99%